Identification of optimal reference genes in Bombyx mori (Lepidoptera) for normalization of stress‐responsive genes after challenge with pesticides. Issue 4 (30th March 2022) - Zhao, Zi‐qin; Zheng, Kai‐yi; Ou, Qi; Xu, Ping‐zhen; Qin, Sheng; Sun, Xia; Li, Mu‐wang; Wu, Yang‐chun; Wang, Xue‐yang
Abstract: Pesticides are frequently used to control pests in agriculture due to their ease of use and effectiveness, but their use causes serious economic losses to sericulture when their production overlaps with agriculture. However, no suitable internal reference genes (RGs) have been reported in the study of silkworms in response to pesticides. In this study, a standard curve was established to detect the expression levels of seven RGs in different tissues of different silkworm strains after feeding with pesticides using reverse transcription quantitative real‐time polymerase chain reaction (RT‐qPCR), including BmGAPDH, BmActin3, BmTBP, BmRPL3, Bm28sRNA, Bmα‐tubulin, and BmUBC, and the stability of them was evaluated by using NormFinder, geNorm, Delta CT, BestKeeper, and RefFinder. The results showed that BmGAPDH and Bmα‐tubulin were relatively stable in the midgut after feeding with fenvalerate, BmGAPDH and Bmactin3 were relatively stable in the fat body, and Bmα‐tubulin and Bmactin3 were relatively stable in the hemolymph, indicating that Bmactin3 was the most suitable RG when evaluating fenvalerate, followed by BmGAPDH and Bmα‐tubulin . Besides, BmGAPDH and Bmactin3 were relatively stable in the midgut after treatment with DDVP, BmGAPDH and Bmα‐tubulin were relatively stable in the fat body, and BmGAPDH and Bmα‐tubulin were relatively stable in the hemolymph, indicating that Bmα‐tubulin was the most stable RG when evaluating DDVP, followed by BmGAPDH and Bmactin3 . Of note, BmGAPDH was shared by the two pesticides. The results will be valuable for RG selection in studying the pesticide response mechanism of silkworms and other lepidopteran insects. Abstract : In this study, seven widely used RGs were analyzed in different tissues of silkworm strains following pesticide treatment, including BmGAPDH, BmActin3, BmTBP, BmRPL3, Bm28sRNA, Bmα‐tubulin, and BmUBC, and the stability of them was evaluated by using NormFinder, geNorm, Delta CT, BestKeeper, and RefFinder. Bmactin3 was the most suitable RG for fenvalerate, Bmα‐tubulin was the most stable RG for DDVP, and BmGAPDH was shared by both of the two pesticides.